Boomerang Strategy and Feminist Resistance: The Case of We Will Stop Femicide Platform in Turkiye - Dewi, Putu Ratih Kumala; Octavianne, Rievca Nesya (SIYAR Journal, 2026)
The increasing rate of femicide in Türkiye has raised serious human rights concerns, yet state responses remain inadequate and often repressive toward civil society organizations. This article analyzes how the We Will Stop Femicide Platform (WWSF), a leading local NGO, formulates and implements its advocacy strategies amidst shrinking civic space and governmental hostility. Drawing on normative feminism theory, Keck and Sikkink’s boomerang pattern and the framework of transnational advocacy networks (TANs), this study explores how WWSF navigates around domestic constraints by forging international alliances to exert external pressure on the Turkish government. This approach allows a contextual and in-depth understanding of the dynamics between local repression and transnational advocacy. This article employs a qualitative research method using literature study, drawing data from academic publications, official reports, news articles, and organizational documents related to WWSF and femicide in Türkiye. The findings reveal that WWSF engages in transnational mobilization through partnerships with international NGOs, global media outreach, and strategic use of international norms, especially following Türkiye’s withdrawal from the Istanbul Convention and state-led efforts to dissolve the organization. This article contributes to the discourse in International Relations by highlighting a bottom-up perspective on global human rights advocacy, emphasizing the agency of non-state actors in challenging authoritarian practices through cross-border solidarity.